Assessment of drone adoption in agriculture in the municipality of Porto Velho, State of Rondônia, Brazil (Research, Society and Development, 2024)
Precision agriculture is gaining prominence globally, with Brazil following this trend. Drones stand out among promising technologies, allowing for the collection of precise data on crops in real-time, facilitating quick and accurate decisions for farmers. However, the adoption of these devices faces challenges, such as the lack of knowledge and training among producers. This study aimed to assess the knowledge and adoption of rural producers in Porto Velho, Rondônia, regarding drones in agriculture. The research was conducted in Ramal São Domingos, with structured questionnaires administered to fifteen rural producers. The results showed that a significant portion of producers has knowledge about drones in agriculture, mainly obtained through the internet. However, lack of experience and the absence of training courses were identified as major barriers to adoption. Perceived purposes for drone use include improvements in agricultural work, mapping, and pesticide application, highlighting advantages such as agility, quality, and mapping. It is concluded that there is a growing interest among rural producers in the use of drones in agriculture, but overcoming identified barriers is necessary to promote broader and more effective adoption. Training and education strategies are essential for farmers to fully harness the potential of drones, contributing to increased productivity and efficiency in the field.